(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the Agriculture Research Farm at Rama University, Mandhana, Kanpur, the current experiment, "Impact of both organic and inorganic sources of nutrients on production and productivity of Indian mustard (Brassica juncea L.)," was carried out from Rabi season 2022–23.